The Relationship Between Mother's Knowledge And Stunting Incidents In Toddlers In The Work Area Of The Sanrobone Health Center - Muthahharah; Hafifa Yahya; Rasmawati; Eka Hadrayani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
Stunting is a physical growth disorder which is characterized by a decrease in growth speed and is the impact of nutritional imbalance. Stunting is still one of the unresolved nutritional problems in children in Indonesia. Stunting can cause long-term impacts, namely disruption of physical, mental, intellectual, and cognitive development. Children who experience stunting will increase the risk of offspring with low birth weight, and will be difficult to correct until the age of 5 years. Mother's knowledge is one of the important things in the process of growth and development in toddlers. Objective: This study aims to determine the relationship between mother's knowledge and the incidence of stunting in children under five in the Sanrobone Health Center, Takalar Regency. Methods: This type of research is a quantitative research with a cross-sectional research design, sampling using multistage random sampling technique. The samples obtained were 93 respondents who met the inclusion criteria. The data collection technique used a questionnaire taken from previous research, namely Gilbert's (2021) research. The statistical test used was chi-square p-value <0.05. Results: The results of the chi-square test showed that there was a relationship between mother's knowledge and the incidence of stunting in toddlers in the Sanrobone Takalar Health Center with p = 0.00 value. Conclusion: From the results of the study it can be concluded that mother's knowledge has a significant relationship to the incidence of stunting in toddlers in the Sanrobone Health Center Work Area, Kab. Takalar.